Interhospital teleproctoring of endovascular intracranial aneurysm treatment using a dedicated live-streaming technology: first experiences during the COVID-19 pandemic. Issue 10 (4th October 2020) - Bechstein, Matthias; Elsheikh, Samer; Wodarg, Fritz; Taschner, Christian A; Hanning, Uta; Buhk, Jan-Hendrik; McDonough, Rosalie; Goebell, Einar; Fiehler, Jens; Bester, Maxim
Abstract : This is a report of the first three cases of endovascular aneurysm treatment that were proctored by a remote interventionalist using a novel high-resolution low-latency streaming technology. The proctor was located in a neurovascular centre and supported the treating interventional teams in two distant cities (up to 800 km/500 miles apart). All aneurysms were treated using the Woven EndoBridge (WEB) embolisation system, either electively or following subarachnoid haemorrhage. On-site proctoring was not possible due to travel restrictions during the COVID-19 pandemic. WEB placement was feasible in all cases. Good rapport between proctors and treating physicians was reported, enabled by the high-resolution image transmission and uninterrupted feedback/discussion via audiostream. No clinical complications were encountered. Short-term follow-up revealed adequate occlusion of all treated aneurysms. The employed streaming technology provided effective remote proctoring during complex aneurysm cases, including the management of technical complications.